Una aproximación a la comercialización de la producción de los concentrados mineros - Ospino edery, Ysaac (2009)
The present article develops a particular analysis on the implication of the commercialization of the production of concentrated minerals for the period of 1989 until the 2007. The volumes embarked (exported) of concentrated minerals in the last 10 years, represent in paid load, the shipping companies foreign amounts equivalent to the required ones to start up one or two refineries, as well as the payments made to refineries in the outside to refine those concentrated. With the application in end, of economic policies of promotion to the investments mining of liberal character, a control/fiscalización to the valuation of the metallurgical mining production is not had which would be allowing the practice of subestimate or on valuation (transference of prices).